2010
DOI: 10.1017/s1751731109991108
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response and carcass and meat quality of suckling lambs in relation to transport time and stocking density during transport by road

Abstract: To evaluate the effect of stocking density and transport time on physiological responses and meat quality, 72 male suckling lambs were transported by road to the slaughterhouse at three different stocking densities (0.12, 0.20 or 0.25 m 2 /lamb) and two transport times (5 h or 30 min). Blood samples were collected pre-transport at the farm and after unloading in the slaughterhouse to measure levels of cortisol, creatine kinase (CK) and lactate dehydrogenase (LDH). After slaughter, the weights of the hot carcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 37 publications
6
30
1
Order By: Relevance
“…In fact, as discussed by Warriss (1990), the mobilisation of tissues to provide energy to maintain vital body functions could result in losses in the weight of liver. The SD did not affect carcass quality, in agreement with results found by De la Fuente et al (2010) in suckling lambs.…”
Section: Carcass Quality and Liver Weightsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, as discussed by Warriss (1990), the mobilisation of tissues to provide energy to maintain vital body functions could result in losses in the weight of liver. The SD did not affect carcass quality, in agreement with results found by De la Fuente et al (2010) in suckling lambs.…”
Section: Carcass Quality and Liver Weightsupporting
confidence: 91%
“…Cooking loss percentage was determined as the loss with respect to the initial weight after cooking the samples for 30 min in plastic bags immersed in a water bath at 75°C according to De la Fuente et al (2010).…”
Section: Carcass and Meat Quality Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight losses have been investigated in small ruminants that differed in age, breed, duration of transport and pre-slaughter fasting (Hall et al, 1997;Kadim et al, 2006;De la Fuente et al, 2010), Dobicki et al (2005). Milewski (2009) also noted a significant increase (P ≤ 0.01) in the percentage of lymphocytes and a tendency towards a lower percentage of neutrophils in the blood of lambs fed diet with dried yeast addition.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, De la Fuente et al (2010) found that lactate dehydrogenase was greater in lambs after a 30 min transport period but lower after a 5 h transport period compared with baseline values. In addition, lactate concentrations of sheep exercised for 2 h on a treadmill at a speed of 4.5 km/h increased by 55% in the first 15 min before declining below baseline levels (Pethick et al, 1987).…”
Section: Discussionmentioning
confidence: 90%